FROM LAB TO LIFE: HOW NANOTECHNOLOGY IS REVOLUTIONIZING CANCER THERAPY - Mansurov Begzod; Fazliddin Arzikulov (Modern American Journals, 2026)
Nanotechnology is increasingly reshaping modern oncology by translating laboratory discoveries into clinically effective cancer therapies. Conventional treatments such as chemotherapy and radiotherapy remain central to cancer care, yet they are often limited by nonspecific drug distribution, systemic toxicity, and treatment resistance. According to the World Health Organization, cancer accounted for nearly 10 million deaths globally in 2020, underscoring the urgent need for more precise and effective therapeutic strategies. Nanotechnology addresses this need by enabling targeted drug delivery, improved diagnostics, and multifunctional treatment platforms that enhance both efficacy and safety. One of the most significant contributions of nanotechnology to cancer therapy is the development of nanoparticle-based drug delivery systems. Nanoformulations such as liposomal doxorubicin and nanoparticle albumin-bound paclitaxel (nab-paclitaxel) have demonstrated clear clinical advantages.
Keywords: Nanotechnology; cancer therapy; nanomedicine; targeted drug delivery; nanoparticle-based therapeutics; cancer diagnostics; theranostics; precision oncology; clinical translation; oncology innovation.